STRENGTHENING RELIGIOUS AND MORAL VALUES IN EARLY CHILDHOOD: A STUDY AT SAYMARA KINDERGARTEN - Rahayu, Watik; Formen , Ali; Isdaryanti , Barokah (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Internalizing religious and moral values, which will guide attitudes and actions, is a crucial aspect at this stage. Religious and moral education not only shapes children's spirituality but also helps them understand the concepts of right and wrong from an early age; Purpose of the Study: This study aims to examine strategies for strengthening religious and moral values ​​applied in the practice of early childhood education institutions; Method: This study used a descriptive qualitative approach. The research location was Kartasura Kindergarten, Sukoharjo, Central Java, which applies a thematic-integrative approach to learning. The research subjects included two class teachers and four children aged 4–6 years. The research informants were the principal and five parents of students, as part of data triangulation. Data were collected through participant observation, in-depth interviews, and documentation. Data were analyzed using a thematic approach based on the model of Miles et al.; Results: The strengthening of religious and moral values ​​at Saymara Kindergarten is reflected in its vision, mission, goals, work programs, and learning activities. These are implemented through unstructured, non-teaching activities, from the moment children enter the school gate until they leave for home. Furthermore, this learning process is further strengthened through both individual and social activities; and Conclusion: religious and moral values are instilled through both unstructured non-learning and more structured learning activities. Both are integrated and reinforce each other, providing children with a strong foundation to face the challenging and unpredictable future.